Detection of amino acid with metamaterial perfect absorbers in the terahertz band. (31st March 2022) - Zhu, Jun; Wu, Changsong
Highlights: The proposed sensor can accurately identify the four amino acids selected in this study. The obtained sensitivity values of modes are 1.1 THz/RIU (9846 nm/RIU) and 1.5 THz/RIU (6962 nm/RIU). The absorptivity values of modes reached 99.86% and 99.99%. The research of this paper has provided an essential reference for further development of metamaterial sensors. Abstract: At present, most amino acid detection techniques have the shortcomings of laborious equipment operation procedures, long detection periods, and low accuracy, which cannot meet the requirements of high-standard amino acid identification in the food industry. Based on the related literature, some amino acids are readily soluble in water. Therefore, a novel detection and identification method can be designed based on the different refractive indices of aqueous amino acid solutions. We introduce a terahertz metamaterial perfect absorber which component successively are a Si buffer layer, a solid metallic Au reflecting layer, a SiO2 depletion layer, a main structure array layer, and a cover layer from bottom to top. The main structure array layer composed of graphene four-opening square ring structure and a golden hemisphere. The absorber achieves perfect absorption based on the principle of impedance matching. It is innovatively applied for the detection of aqueous amino acid additives solution. The absorber has two modes with absorptivity of 99.86% and 99.99% at 5.9 THz and 8.1 THz, respectively. The sensing sensitivity of both modes can reaches 1.1 THz/RIU and 1.5 THz/RIU, respectively, which has obvious advantages in other reported sensors. Experimental results show that the proposed sensor can accurately identify the four amino acids selected by 100% in this study. The research presented this paper provides an essential reference for further development of metamaterial sensors.